2021
DOI: 10.1016/j.mito.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Stress and circulating cell-free mitochondrial DNA: A systematic review of human studies, physiological considerations, and technical recommendations

Abstract: Cell-free mitochondrial DNA (cf-mtDNA) is a marker of inflammatory disease and a predictor of mortality, but little is known about cf-mtDNA in relation to psychobiology. A systematic review of the literature reveals that blood cf-mtDNA varies in response to common real-world stressors including psychopathology, acute psychological stress, and exercise. Moreover, cf-mtDNA is inducible within minutes and exhibits high intra-individual day-to-day variation, highlighting the dynamic regulation of cf-mtDNA levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 203 publications
5
90
0
Order By: Relevance
“…Otherwise, cf-mtDNA may be removed via the liver, spleen, or kidney [62,75]. In septic patients with kidney injuries, cf-mtDNA levels are elevated in urine but not in plasma, supporting the idea that urine is a possible mechanism of cf-mtDNA elimination [76].…”
Section: Release Forms and Detection Of Cf-mtdna 41 Mechanisms Of Release And Removal Of Cf-mtdnamentioning
confidence: 93%
“…Otherwise, cf-mtDNA may be removed via the liver, spleen, or kidney [62,75]. In septic patients with kidney injuries, cf-mtDNA levels are elevated in urine but not in plasma, supporting the idea that urine is a possible mechanism of cf-mtDNA elimination [76].…”
Section: Release Forms and Detection Of Cf-mtdna 41 Mechanisms Of Release And Removal Of Cf-mtdnamentioning
confidence: 93%
“…Interestingly, 5-HT 3 receptors are present in mitochondrial membranes, where they augment calcium ion uptake in hypoxia and increase the respiration control ratio in mice [ 342 ]. Furthermore, emerging studies revealed that blood in the normal physiological state contains whole functional cell-free mitochondria [ 343 , 344 ]. This observation may have profound implications for the field of inflammation and clinical applications [ 343 ], potentially involving signaling via 5-HT 3 receptors present in these mitochondrial membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging studies revealed that blood in the normal physiological state contains whole functional cell-free mitochondria [ 343 , 344 ]. This observation may have profound implications for the field of inflammation and clinical applications [ 343 ], potentially involving signaling via 5-HT 3 receptors present in these mitochondrial membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ccf-mtDNA has been reported in various somatic disorders including sepsis, diabetes, and traumatic injury [ 2 5 ]. Recent studies show that also psychological stress may trigger ccf-mtDNA release [ 1 , 6 , 7 ], suggesting that this biomarker might be useful in certain psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…While these findings suggest that depression and suicidality may be accompanied by increased amounts of cellular stress, other studies have reported unchanged [ 10 , 11 ], or decreased [ 12 ] ccf-mtDNA in mood disorders compared to healthy controls. As recently reviewed elsewhere [ 1 ], there are several factors relating to assay methodology and study design that might explain divergent findings across studies. Moreover, the use of psychotropic medications may influence mitochondrial function and cellular health [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%